Creating joint representations of collaborative problem solving with multi‐touch technology. (10th February 2014) - Mercier, E.; Higgins, S.
<x xml:space="preserve">Abstract</x> Multi‐touch surfaces have the potential to change the nature of computer‐supported collaborative learning, allowing more equitable access to shared digital content. In this paper, we explore how large multi‐touch tables can be used by groups of students as an external representation of their group interaction processes. Video data from 24 groups of students working on a logic reasoning problem was examined to identify their levels of reasoning about the task, and how they used the table to support their reasoning. Results indicate that of the 13 groups who solved or nearly solved the problem, 12 used the table to represent their reasoning process, while only four groups who used the table to support their reasoning process did not solve the problem. Examples from three groups are used to explore the different ways the table was used as an external representation of the groups' processes. The findings indicate that the group problem‐solving process can be enhanced with the use of multi‐touch tables, although students may need support in using the technology effectively to support their collaborative reasoning.